An Analysis of Ideational Metafunction on News Jakarta Post about Some Good Covid-19 Related News - Elisabet Hutabarat; Herman Herman; Dumaris E Silalahi; Partohap Saut Raja Sihombing (Universitas Hamzanwadi, 2020)
This research intended to find out components of transitive system used on news Jakarta post about some good Covid-19 related news. Therefore, the researcher formulated a question as the problem as follows: â€œWhat are components of transitive system used on news Jakarta post about some good Covid-19 related news?â€ The researcher used qualitative design because data are collected by using documents in form of word and a procedure of systematic analysis of content text (words, phrase, documents, etc.), analysis content by qualitative enable researchers to understand the text by grouping words that have same meaning into categories. The research finding showed that component of transitivity system. There are three transitive system namely participants, process, and circumstances. First, participants found namely goal, actor, sayer, senser, verbiage, value, token carrier, attribute, behaver, client, recipient, phenomenon, and receiver with calculate is 177 participants, the highest participant is actor (26.55%). The second process found material, mental, verbal, behavioral, relational with calculate is 103 processes, the highest process is material (44.67%). The third, circumstance found extent, locution, contingency, manner, matter, and role, with calculates are 80 times. The highest circumstance is extents or time (30 %).